Finite-time synchronization of Kuramoto-oscillator networks with a pacemaker based on cyber-physical system - Rao, Pengchun; Guo, Xiufeng (Frontiers in Physics, 2022)
In this paper, we study the finite-time synchronization problem of a Kuramoto-oscillator network with a pacemaker. By constructing a cyber-physical system (CPS), the finite-time phase agreement and frequency synchronization of the network are explored for identical and non-identical oscillators, respectively. According to the Lyapunov stability analysis, sufficient conditions are deduced for ensuring the phase agreement and frequency synchronization for arbitrary initial phases and/or frequencies under distributed strategies. Furthermore, the upper bound estimations of convergence time are obtained accordingly, which is related to the initial phases and/or frequencies of oscillators. Finally, numerical examples are presented to verify the effectiveness of the theoretical results.